2020
DOI: 10.9734/jemt/2020/v26i1030295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustainability Reporting on Economic Value Added of Manufacturing Firms Listed on Nigeria Stock Exchange

Abstract: This study assessed the Effect of Sustainability Reporting on Economic Value Added of Manufacturing Firms Listed on Nigeria Stock Exchange. Twenty one (21) listed manufacturing firms constituted the sample size of this study between 2008 and 2019. Ex-Post facto research design and content analysis were adopted while secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10 statistical software. The study employed descriptive statistics and infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
1
2
1
Order By: Relevance
“…This indicates a lack of commitment on the part of management to create value for the owners of the businesses (maximising shareholders' wealth) through the disclosure of sustainability information. The outcome contradicted the earlier findings of Amahalu ( 2018), Ikechukwu &Blessing (2020), andIliemena et al (2023), whose findings revealed that SR exerts a positive and significant influence on EVA and supported the finding of Purwanti (2020), and Schiessl et al ( 2022) that SR has an insignificant impact of EVA.…”
Section: Two-step System Gmm On the Effect Of Sr On Cp Of Listed Cons...contrasting
confidence: 78%
See 3 more Smart Citations
“…This indicates a lack of commitment on the part of management to create value for the owners of the businesses (maximising shareholders' wealth) through the disclosure of sustainability information. The outcome contradicted the earlier findings of Amahalu ( 2018), Ikechukwu &Blessing (2020), andIliemena et al (2023), whose findings revealed that SR exerts a positive and significant influence on EVA and supported the finding of Purwanti (2020), and Schiessl et al ( 2022) that SR has an insignificant impact of EVA.…”
Section: Two-step System Gmm On the Effect Of Sr On Cp Of Listed Cons...contrasting
confidence: 78%
“…Similarly, the Table shows that SRD exerts a negative and insignificant impact on EVA, as evidenced by a coefficient of -0.408 and a p-value of 0.521. This implies that an increase in the level of disclosure by these companies will result in a decrease of about N0.408 of EVA, holding all other factors constant as in the earlier findings of Amahalu (2018) and Okoye & Ndum (2020) whose findings revealed that SR exerts a positive and significant influence on EVA, and supported that of Purwanti (2020), andOgochukwu &Grace (2022). Firms' size and leverage were all found to have an insignificant impact on ROE, though that of leverage is negative.…”
Section: Two-step System Gmm On the Effect Of Sr On Cp Of Listed Indu...supporting
confidence: 71%
See 2 more Smart Citations